Decrease of O2 deficit is a potential factor in increased time to exhaustion after specific endurance training - Demarle, A. P.; Slawinski, J. J.; Laffite, L. P.; Bocquet, V. G.; Koralsztein, J. P.; Billat, V. L. (Journal of Applied Physiology, 2001)
The main purpose of this study was to investigate the effects of an 8-wk severe interval training program on the parameters of oxygen uptake kinetics, such as the oxygen deficit and the slow component, and their potential consequences on the time until exhaustion in a severe run performed at the same absolute velocity before and after training. Six endurance-trained runners performed, on a 400-m synthetic track, an incremental test and an all-out test, at 93% of the velocity at maximal oxygen consumption, to assess the time until exhaustion. These tests were carried out before and after 8 wk of a severe interval training program, which was composed of two sessions of interval training at 93% of the velocity at maximal oxygen consumption and three recovery sessions of continuous training at 60-70% of the velocity at maximal oxygen consumption per week. Neither the oxygen deficit nor the slow component were correlated with the time until exhaustion (r = 0.300, P = 0.24, n = 18 vs. r = 0.420, P = 0.09, n = 18, respectively). After training, the oxygen deficit significantly decreased (P = 0.02), and the slow component did not change (P = 0.44). Only three subjects greatly improved their time until exhaustion (by 10, 24, and 101%). The changes of oxygen deficit were significantly correlated with the changes of time until exhaustion (r = 0.911, P = 0.01, n = 6). It was concluded that the decrease of oxygen deficit was a potential factor for the increase of time until exhaustion in a severe run performed after a specific endurance-training program.